Efek Antidiare Ekstrak Air Bunga Nagasari (Mesua Ferrea L.) Terhadap Mencit BALB/c yang Diinduksi Minyak Jarak - Putu Monik Ananta Puspitarini; Iman Surya Pratama; Bambang Fajar Suryadi (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Nagasari (Mesua ferrea L.) has a empirically repute for management of diarrhea in West Nusa Tenggara Province. However, the safety and efficacy of the nagasari flowers extract have not been scientifically validated in animal model. This study wasaimed to investigate the antidiarrheal effect of water extract of the nagasari flowers in BALB/c mice. The antidiarrhea activity of nagasari flowerswas investigated using castor oil-induced diarrhea increase in diarrhea index in mice.In castor oil-induced diarrhea test, mice received various consentrations of nagasari flowers extract (0,4% w/v; 0,8% w/v; and 1,6% w/v), where as negative controls received CMC-Na 1% and positive controls received loperamide 0,7 mg/kgBW orally once daily for 1 day and the mice droppings were observed. The phytochemical screening of nagasari flowers contain flavonoid, saponin, and phenolic. Water extract of nagasari flowers at concentration 1,6% showed significant inhibitory activity against castor oil-induced diarrhea when compared with positive controls (diarrhea index 0,083 ; p>0,05). Therefore, this study provides a scientific support for the acclaimed traditional use water extract of Mesua ferrea L. for the treatment of diarrheal diseases.